2x^2-5x+3=0 用因式分解法
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 08:13:04
2x^2-5x+3=0用因式分解法2x^2-5x+3=0用因式分解法2x^2-5x+3=0用因式分解法2x^2-5x+3=0(2x-3)(x-1)=02x-3=0或x-1=0x1=3/2x2=12x&
2x^2-5x+3=0 用因式分解法
2x^2-5x+3=0 用因式分解法
2x^2-5x+3=0 用因式分解法
2x^2-5x+3=0
(2x-3)(x-1)=0
2x-3=0 或 x-1=0
x1=3/2 x2=1
2x²-5x+3=0
(x-1)(2x-3)=0
x=1或x=3/2
X²-3X+1=0用因式分解法 5X²+2X-1=0用因式分解法
(x+5)方+3(x+5)-4=0用因式分解法 9(x-1)方=(2x+1)方 用因式分解法
4x^2-3x=0因式分解法
3(2X+1)=X(X+1) 用因式分解法解方程.必须用因式分解法.3(2X+1)=X(X+1) 用因式分解法解方程.必须用因式分解法.
2x^2-5x+3=0 用因式分解法
2(3x+1)的平方-5(3x+1)=0 用因式分解法
用因式分解法解(3x+1)(2x-5)=0这个方程
因式分解法3(x-2)=x(x-2)
(2x-3)^2-81=0因式分解法
5x(2x+3)=2(2x+3)用因式分解法怎么解
用因式分解法解下列方程 (x-3)^2+2x (x-3)=0
(x-3)^2+2x(x-3)=0用因式分解法怎么做?
2(x-3)^2-x(x-3)=0用因式分解法
用因式分解法解方程;(x-3)的平方+2x(x-3)=0
用因式分解法解方程 2x(5x-1)=3(5x-1)
2x(x-3)=5(x-3)用因式分解法怎么求!
x(3x-2)-6x²=0 用因式分解法解方程
5x(x-3)=6-2x(用因式分解法算)